Beams with the transverse-only intensity at the focus - S.S. Stafeev; N.N. Kazakov; V.V. Kotlyar (Компьютерная оптика)
In this work, sharp focusing of vector beams with azimuthal polarization and beams with V-line of polarization uncertainty is simulated numerically using the Richards-Wolf formulas. It is demonstrated that at the sharp focus of these beams the longitudinal component of the electric field vector is zero. Previously, a similar effect was demonstrated only for azimuthally polarized beams. Also, the longitudinal component of the spin angular momentum of these beams is calculated and the possibility of creating sector azimuthally polarized beams using vector waveplates is shown.